2022
DOI: 10.3390/pr10040621
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Protein and Non-Protein Nitrogen Compounds during Fishmeal Processing—Identification of Unoptimized Processing Steps

Abstract: Quality changes of protein and non-protein nitrogen compounds during industrial fishmeal processing of fatty pelagic species (mackerel/herring rest material blend, MHB) and lean fish (whole blue whiting, BW) were studied to identify processing steps that require optimization to allow production of products for human consumption. Samples from protein-rich processing streams throughout the fishmeal production were analyzed for proximate composition, salt soluble protein content (SSP), biogenic amines (BA), total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The amount of protein in fish muscles is affected by their moisture and fat content, as the percentage of protein is inversely related to the percentage of moisture and fat, and these percentages are not fixed because they vary based on age, size, feeding and fishing season, physical activity and sexual status [22]. The reasons for the difference in protein ratios in this study may be due to their influence by several factors, including the autolysis of protein by autoenzymes found in fish meat of various species and volatilization of quantities of volatile nitrogenous bases formed during transport and storage [23]. Furthermore, Hamilton et al [24] showed that the protein content in the muscles of Atlantic salmon ranges from 16-21.…”
Section: Chemical Qualities 311 Chemical Analysis Of Body Components ...mentioning
confidence: 85%
“…The amount of protein in fish muscles is affected by their moisture and fat content, as the percentage of protein is inversely related to the percentage of moisture and fat, and these percentages are not fixed because they vary based on age, size, feeding and fishing season, physical activity and sexual status [22]. The reasons for the difference in protein ratios in this study may be due to their influence by several factors, including the autolysis of protein by autoenzymes found in fish meat of various species and volatilization of quantities of volatile nitrogenous bases formed during transport and storage [23]. Furthermore, Hamilton et al [24] showed that the protein content in the muscles of Atlantic salmon ranges from 16-21.…”
Section: Chemical Qualities 311 Chemical Analysis Of Body Components ...mentioning
confidence: 85%